Photothermal actuated origamis based on graphene oxide–cellulose programmable bilayers. Issue 4 (17th February 2020) - Gao, Dace; Lin, Meng-Fang; Xiong, Jiaqing; Li, Shaohui; Lou, Shi Nee; Liu, Yizhi; Ciou, Jing-Hao; Zhou, Xinran; Lee, Pooi See
Abstract : The combination of graphene oxide and cellulose produces shape programmable active origamis, which are able to transform among their multi-stable morphs, including 3D soft robotic architectures, mechanical metamaterials and biomimetic analogies. Abstract : The design and construction of 3D architectures enabled by stimuli-responsive soft materials can yield novel functionalities for next generation soft-bodied actuating devices. Apart from additive manufacturing processes, origami inspired technology offers an alternative approach to fabricate 3D actuators from planar materials. Here we report a class of near-infrared (NIR) responsive 3D active origamis that deploy, actuate and transform between multistable structural equilibria. By exploiting the nonlinear coefficient of thermal expansion (CTE) of graphene oxide (GO), graphene oxide/ethylene cellulose (GO/EC) bilayers are readily fabricated to deliver precise origami structure control, and rapid low-temperature-triggered photothermal actuation. Complexity in 3D shapes is produced through heterogeneously patterning GO domains on 2D EC thin films, which allows us to customize 3D architectures that adapt to various robotic functions. The strategy also enables the construction of material systems possessing naturally inaccessible properties, such as remotely controlled mechanical metamaterials with auxetic behavior and bionic flowers with a rapid blooming rate. Harnessing deformability with multiple degrees of freedom (DOF) upon light irradiation, this work leads to breakthroughs in the design and implementation of shape-morphing functions with soft origamis.